A DFT Mechanistic Study on Base-Catalyzed Cleavage of the β-O-4 Ether Linkage in Lignin: Implications for Selective Lignin Depolymerization - Mensah, Mary; Tia, Richard; Adei, Evans; de Leeuw, Nora H. (Frontiers in Chemistry, 2022)
The detailed mechanism of the base-catalyzed C-C and C-O bond cleavage of a model compound representing the β-O-4 linkage in lignin is elucidated using DFT calculations at the M06/6-31G* level of theory. Two types of this linkage have been studied, a C2 type which contains no γ-carbinol group and a C3 type which contains a γ-carbinol. Cleavage of the C2 substrate is seen to proceed via a 6-membered transition structure involving the cation of the base, the hydroxide ion and the α-carbon adjacent to the ether bond. The reaction with KOH has the lowest activation barrier of 6.1 kcal mol−1 with a calculated rate constant of 2.1 × 108 s−1. Cleavage of the C3 substrate is found to proceed via two pathways: an enol-formation pathway and an epoxide-formation pathway. The first path is the thermodynamically favored pathway which is similar to the pathway for the C2 substrate and is the preferred pathway for the isolation of an enol-containing monomer. The second path is the kinetically favored pathway, which proceeds via an 8-membered transition state involving a hydrogen hopping event, and is the preferred pathway for the isolation of an epoxide-containing monomer. The KOH-catalyzed reaction also has the lowest activation barrier of 10.1 kcal mol−1 along the first path and 3.9 kcal mol−1 along the second path, with calculated rate constants of 2.4 × 105s−1 and 8.6 × 109s−1 respectively. Overall, the results provide clarity on the mechanism for the base-catalyzed depolymerization of lignin to phenolic monomers. The results also suggest both NaOH and KOH to be the preferred catalysts for the cleavage of the β-O-4 linkage in lignin.